THE GRAPHIC EDITING AND VISUAL COMMUNICATION IN PRINT JOURNALISM MAGAZINE: A CASE STUDY OF VEJA’S FRONT-PAGES IN 2010 ELECTIONS - Norberto Ribeiro Soares, Filipe; Camargo, Celi (Revista Gênero e Interdisciplinaridade, 2023)
This study shows a brief historic of the newsmagazine in Brazil, putting special attention to the contexts of their emerging and propagation in the country .The empirical base aim to do a graphic analysis of the magazine Veja during the elective process in 2010, with the objective of explore the choice and application of visual communication’s aspects on Veja’s front-pages.